High-Stiffness Torque Sensor With a Strain Amplification Mechanism for Cooperative Industrial Manipulators - Kim, Uikyum; Maeng, Chan-Young; Bak, Geonho; Kim, Yong-Jae (IEEE transactions on industrial electronics (1982), 2022)
This study presents a high-stiffness torque sensor with a strain amplification mechanism for cooperative industrial manipulators. A novel strain amplification mechanism for a torque sensor has been designed to increase the stiffness of the sensor. The mechanism has a single structure composed of trapezoidal beams, flexure structures, and inner and outer frames. In this configuration, the displacement that occurs in the beam is amplified by the flexure structure. The amplified displacement is measured using capacitance sensing technology. As a result, the developed torque sensor has a high stiffness (198.7 kN · m/rad) and compactness (diameter of 110 mm and a thickness of 9.8 mm) that integrates with all the electronics. Additionally, it has a low cost and it is easy to manufacture. Through several experimental setups, we evaluated the sensing performances of the sensor with regard to accuracy, high stiffness, and repeatability.